Odpowiedzi

Najlepsza Odpowiedź!
2010-01-17T16:17:35+01:00
=
x+x+2y-4y=-3+5
-3x-x+8y+6y=4-5

2x-2y=2 /:2
-4x+14y=-1

x-y=1→x=1+y
-4(1+y)+14y=-1

x=1+y
-4-4y+14y=-1

10y=-1+4
10y=3
y=0,3

x=1+y=1+0,3=1,3

spr.1,3-0,3=1
1=1

-4×1,3+14×0,3=-1
-5,2+4,2=-1
-1=-1
2010-01-17T16:32:46+01:00
X+2y-5=4y-x-3
-3x+8y+5=x-6y+4


x+x+2y-4y=5-3
-3x-x+8y+6y=4-5

2x-2y=2 /*2 ------> 2x- 2(-3/18)= 2
-4x+14y=-1 2x + 6/18 =2
2x= 2-6/18
4x-2y=4 2x= 1 12/18 /:2
-4x-14y=-1 x= 30/36 = 15/18
+____________
-16y=3 /: (-16)
y= -3/18 (jako ułamek- ukośnik to kreska ułąmkowa)